ORGANIC FERTILIZERS AND THEIR PROPERTIES (World Bulletin of Social Sciences, 2024)
This article provides analytical information on the characteristics of organic fertilizers and their effect on the regime of nutrients in the soil.
Keywords: Manure; compost; nitrogen; phosphorus